2021
DOI: 10.3389/fonc.2021.727583
|View full text |Cite
|
Sign up to set email alerts
|

CCL23 in Balancing the Act of Endoplasmic Reticulum Stress and Antitumor Immunity in Hepatocellular Carcinoma

Abstract: Endoplasmic reticulum (ER) stress is a cellular process in response to stress stimuli in protecting functional activities. However, sustained hyperactive ER stress influences tumor growth and development. Hepatocytes are enriched with ER and highly susceptible to ER perturbations and stress, which contribute to immunosuppression and the development of aggressive and drug-resistant hepatocellular carcinoma (HCC). ER stress-induced inflammation and tumor-derived chemokines influence the immune cell composition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 75 publications
2
8
0
Order By: Relevance
“…CCL24 which exhibits a high expression level in several types of cancer, this study found that it is underexpressed in breast cancer with no significant relation with OS. Again previous works have shown that a reduction in the chemokine CCL23 in hepatic tumours is linked to a poor prognosis for HCC patients and may be a strategy used by the tumour cells to avoid the immune system [37]. The current study also confirms these results evident from the expression profile and Survival analysis.…”
Section: Discussionsupporting
confidence: 89%
“…CCL24 which exhibits a high expression level in several types of cancer, this study found that it is underexpressed in breast cancer with no significant relation with OS. Again previous works have shown that a reduction in the chemokine CCL23 in hepatic tumours is linked to a poor prognosis for HCC patients and may be a strategy used by the tumour cells to avoid the immune system [37]. The current study also confirms these results evident from the expression profile and Survival analysis.…”
Section: Discussionsupporting
confidence: 89%
“…Previously, we hypothesized that CCL23 might be a stress-related chemokine and an elevated CCL23 may help promote antitumor immunity. 36 Indeed, overexpression of CCL23 is associated with liver cancer suppression, 37 and an elevated serum level of CCL23 was linked with reduced risk factors in gastric cancer. 38 However, CCL23 is a relatively lesser characterized chemokine whose role in cancer suppression remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…CCL23, also known as macrophage inflammatory protein‐3, was the only observed chemokine showing race‐ and cancer‐specific differences with significantly high serum levels of CCL23 in CA men than AA, whereas CCL23 was significantly low in cases with respective races. Previously, we hypothesized that CCL23 might be a stress‐related chemokine and an elevated CCL23 may help promote antitumor immunity 36 . Indeed, overexpression of CCL23 is associated with liver cancer suppression, 37 and an elevated serum level of CCL23 was linked with reduced risk factors in gastric cancer 38 .…”
Section: Discussionmentioning
confidence: 99%
“…To find the association between the CSF proteins and autistic traits in twins diagnosed with ASD and other neurodevelopmental disorders, a study measured 203 proteins in cerebrospinal fluid (n=86, ASD=19, neurotypical=41). The autistic traits correlated significantly with four CSF proteins (Smedler et al, 2021): C-C motif chemokine ligand 23 (CCL23) – a chemokine active on immune cells like T lymphocytes and monocytes (Karan, 2021). Agouti-related protein (AGRP) – synthesized in hypothalamic neurons that are involved in energy metabolism and appetite. Chitinase-3-like protein 1 (CHI3L1) – protein marker of inflammation. Lipopolysaccharide-induced TNF-α factor (LITAF). CCL23, AGRP, CHI3L1 correlated negatively, and LITAF correlated positively with autistic traits.…”
Section: Methodsmentioning
confidence: 99%
“…1. C-C motif chemokine ligand 23 (CCL23) -a chemokine active on immune cells like T lymphocytes and monocytes (Karan, 2021).…”
Section: Presence Of Neuroinflammation Markers In Csfmentioning
confidence: 99%